Pengaruh Kualitas Produk, Promosi dan Kualitas Pelayanan Terhadap Loyalitas Nasabah di PT. Bank Rakyat Indonesia KCP Kota Wisata Kabupaten Bogor - Ibnu Haris Nasution; Agtovia Frimayasa (Prisani Cendekia, 2022)
This research aims to see the analysis of the quality of promotion and service quality on customer loyalty of Bank BRI KCP Tourism City, Bogor Regency. The form of the research is associative with the population being all customers who are savers at the BRI KCP bank, Bogor Regency, which amount to 10,000 customers. Sampling with the slovin formula to obtain a sample of 200 customers. The method of analysis is carried out by stratified regression. This is intended to see the relationship of variables to other variables directly or indirectly or through intermediate variables. This research is a type of field research that uses quantitative methods. The type of data used in this study is primary data which is assisted by the SPSS program. Data collection was taken from the results of distributing questionnaires to 100 respondents. The sampling technique used in this study is the Accidental Sampling method and this study uses multiple linear regression data analysis techniques. The results of this study indicate that the product quality variable (X1) partially has no effect on customer loyalty, while the promotion variable (X2) and service quality variable (X3) partially has a positive and significant effect on customer loyalty at PT. Bank BRI KCP Kotawisata, Bogor Regency.